Training competences of novice researchers from strengthen researcher´s views - Fontaines-Ruiz, Tomas (2018)
The purpose of this study was to reveal the conceptions that expert researchers have about novel researcher’s competences. The study was descriptive, with a mixed design. The data comes from a textual corpus constructed from 78 Prometeo researchers’ opinions about the type of knowledge and skills that novel researchers need. The results revealed two competences cores: the prosocial-emotional and methodological-discursive-technological competences. The expert researchers emphasized the socio-emotional character of research as the need to release the methodological practices from the dogmatism and the passions of the instructors.Novel researchers must have emotional consciousness, openness to methodical plurality, ability to use efficiently technology in favor to their research studies, and discursive quality for the socialization of knowledge.